PEMBERDAYAAN DESA MODEL DESA MANDIRI SEHAT DI KECAMATAN SALAMAN KABUPATEN MAGELANG - Martini, Rina (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2009)
One of goverments efforts to improve villageâ€™s capability to be self help is the establishment of â€œDesa Mandiriâ€ program. Assertion of â€œDesa Mandiriâ€ program as one of govermentâ€™s policy is based on consideration that there is a need to reduce villageâ€™s dependency on central goverment. Goverment cannot be expected to wholly help, subsidize, and facilitate village community anymore, and village community has to start to learn to be independent. There are some models of â€œDesa Mandiriâ€ program, one of them is â€œDesa Mandiri Sehatâ€ or â€œHealthy Self-Help Villageâ€. Jabangsari and Banjarharjo in Salaman Sub-district are amongst those that are successful in implementing â€œDesa Mandiri Sehatâ€. Although there is difference in term of implementation, the success of these villages are relevant to be used for lesson learning and drawing.